Phenotypic variation and epigenetic insight into tissue culture berry crops - Debnath, Samir C.; Ghosh, Amrita (Frontiers in Plant Science, 2022)
Berry crops, a nutrient powerhouse for antioxidant properties, have long been enjoyed as a health promoting delicious food. Significant progress has been achieved for the propagation of berry crops using tissue culture techniques. Although bioreactor micropropagation has been developed as a cost effective propagation technology for berry crops, genetic stability can be a problem for commercial micropropagation that can be monitored at morphological, biochemical and molecular levels. Somaclonal variations, both genetic and epigenetic, in tissue culture regenerants, are influenced by different factors, such as, donor genotype, explant type and origin, chimeral tissues, culture media type, concentration and combination of plant growth regulators, and culture conditions and period. Tissue culture regenerants in berry crops show increased vegetative growth, rhizome production and berry yield containing higher antioxidant activity in fruits and leaves that might be due to epigenetic variation. The present review provides an in-depth study on various aspects of phenotypic variation in micropropagated berry plants and the epigenetic effects on these variations along with the role of DNA methylation, to fill the existing gap in literature.